THE RELATIONSHIP BETWEEN THE INTEREST OF LEARNING, PARENTS ATTENTION AND THE NUMERICAL SKILLS WITH STUDENTS MATHEMATICS LEARNING OUTCOMES OF SMA NEGERI 1 SAPURAN - Diyah Istriani; Suparman Suparman (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
The results of mathematics students learning associated with many factors. Interest in learning, parent’s attention, and numerical skills are a variety of factors that were related to student mathematics learning outcomes. Therefore, this study aimed to determine the relationship between interest in learning, attention parents and numerical skills with mathematics students learning outcomes of class X MIPA SMA Negeri 1 Sapuran Wonosobo district at academic year 2015/2016. The population in this study were all students of class X MIPA SMA Negeri 1 Sapuran comprising five classes with the number of population in this study were 129 students, the sample is class X MIPA 2 totaling 27 students, as well as the technique of sampling with random sampling technique to class. Techniques of data collection was conducted by questionnaire to determine interest in learning and attention from their parents, as well as the test method to determine the ability of numerical and mathematical learning outcomes of students. To test the validity of the instruments used to test the validity, reliability test and different power. After all the data collected do the data analysis techniques including normality test, linearity test, and independent testing. Analysis of data to test the hypothesis by using product-moment correlation and multiple linear regression analysis. The results showed that there was a positive and significant correlation between interest in learning, parents attention and numerical skills with mathematics learning outcomes at a significant level of 5% with a multiple correlation coefficient  and arithmetic    greater than table F  , relative contribution   %, the relative contribution     and the relative contributions    and the effective contribution   %, the effective contribution    and the effective contribution   .